Effects of demineralization on the composition of microalgae pyrolysis volatiles in py-GC–MS. (1st January 2022) - Niu, Qi; Ghysels, Stef; Wu, Nannan; Rousseau, Diederik P.L.; Pieters, Jan; Prins, Wolter; Ronsse, Frederik
Highlights: Acid leaching breaks down the chemical structure of carbohydrates and proteins. Pretreatment effects on pyrolysis volatiles have been discussed. Removal of inorganics increased the relative yields in aromatics and aliphatics. Influence of water-soluble and acid-soluble AAEM species was discussed. Interactions between microalgae components and AAEMs catalysis were elucidated. Abstract: This study compared the volatiles distribution in analytical scale pyrolysis (py-GC–MS) of Nannochloropsis gaditana (marine microalgae) and Scenedesmus almeriensis (freshwater microalgae) and their demineralized counterparts. The role of inorganic elements and their removal via ultrasonic treatment, water washing and (in)organic acid leaching were elucidated. Principal component analysis (PCA) and grey relational analysis were applied to analyze the pyrolysis volatiles distribution and demonstrate the influence of inorganic elements in pyrolysis, respectively. Demineralization affects (breaks down) the chemical structure of carbohydrates, followed by (to a lesser extent) proteins and lipids. Acid leaching promoted hydrolysis and suppressed the catalytic effect associated to inorganic elements in subsequent pyrolysis, compared to ultrasonic treatment and water washing. Elements like K and Na had a larger catalytic influence on microalgae pyrolysis than Ca and Mg. The composition and pyrolytic formation mechanism of major product groups at 500 °C were studied, including anhydrosugars, phenolics, furans, carboxylic acids, alcohols, aliphatic hydrocarbons, aromatic hydrocarbons, N-heterocyclic compounds, nitriles and amides. The results indicate that demineralization shows positive effects on fast pyrolysis of microalgae: (1) by disrupting the cell wall and releasing the lipids and cellular contents. Based on the py-GC–MS peak area normalized to sample mass, the relative contribution of hydrocarbons in the pyrolysis vapors increased from 25.5 % (NG: Nannochloropsis gaditana ) to 32.1 % (NG-HCl: Nannochloropsis gaditana, HCl treated), and from 16.1 % (SA: Scenedesmus almeriensis ) to 22.4 % (SA-HCl: Scenedesmus almeriensis, HCl treated); (2) by decreasing the relative yields in O-containing compounds resulting from the suppressed catalytic effects of alkali and alkaline earth metals (53.3 % (NG) to 37.1 % (NG-HCl), 57.5 % (SA) to 47.8 % (SA-HCl)) that would otherwise have been present in non-demineralized microalgae feedstock. The effects of demineralization on the denitrogenation of pyrolysis vapors were not that obvious. Suggestions for potential full scale applications have been proposed.